Alcoholism among male patients attending emergency units, Baghdad, Iraq - Hashism, Mushtaq T. (Journal of the Faculty of Medicine Baghdad, 2011)
Background: The problem of excessive alcohol consumption is a major cause of public health concern in most countries of the world today. Royal Colleges of Physicians and Psychiatrists recommended that every inpatient should be screened with a questionnaire for alcohol related problems. Therefore, this work was carried out to report on alcoholism in the emergency unit in two general hospitals in Baghdad, Iraq.Methods: The study was carried out in Al-Sader general hospital (Al-Sader city, Baghdad) and Baghdad teaching hospital (Baghdad) for the period 1st July 2008 to 1st May 2009. Data collection was two days per week. Version of 25 items Michigan Alcoholism Screening Test (MAST) and semi-structured schedule based on Diagnostic and Statistical Manual of Mental Disorders, 4th edition (DSM-IV) criteria for alcohol dependence were used. Males aged 16 – 70 years attended emergency units were included in the study.Results: There were 11% had alcoholism. Alcoholism was significantly associated with age > 40 years, married, low educated and employed (p= 0.02, 0.002, 0.03, respectively). Alcohol dependence was significantly associated with younger age (< 40 years), single, low educated, early onset of drinking (